2013
DOI: 10.4049/jimmunol.1300856
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell–Restricted, Tetramer-Forming Tryptases Induce Aggrecanolysis in Articular Cartilage by Activating Matrix Metalloproteinase-3 and -13 Zymogens

Abstract: Mouse mast cell protease (mMCP)-6-null C57BL/6 mice lost less aggrecan proteoglycan from the extracellular matrix of their articular cartilage during inflammatory arthritis than wild-type (WT) C57BL/6 mice, suggesting that this mast cell (MC)-specific mouse tryptase plays prominent roles in articular cartilage catabolism. We used ex vivo mouse femoral head explants to determine how mMCP-6 and its human ortholog hTryptase-β mediate aggrecanolysis. Exposure of the explants to recombinant hTryptase-β, recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…Tryptase functions are mostly mediated by signalling via the PAR-2 receptor [70], [71], [73][75] and by activating other proteases such as collagenases [31], [72]. Additional analyses showed that the MC content of tryptase was significantly up-regulated in perifollicular MCs in lesional AA skin compared to controls ( Figure 2E–I ).…”
Section: Resultsmentioning
confidence: 92%
“…Tryptase functions are mostly mediated by signalling via the PAR-2 receptor [70], [71], [73][75] and by activating other proteases such as collagenases [31], [72]. Additional analyses showed that the MC content of tryptase was significantly up-regulated in perifollicular MCs in lesional AA skin compared to controls ( Figure 2E–I ).…”
Section: Resultsmentioning
confidence: 92%
“…A number of the MC’s serine proteases also can activate numerous metalloproteinase (MMP) zymogens (Lees, Taylor, & Woolley, 1994; Lin et al, 2011; Magarinos et al, 2013). Tetramer-forming MC tryptases, for example, can activate pro-stromelysin/MMP3 which, in turn, can activate latent procollagenase (Gruber et al, 1989) to ultimately cause connective tissue remodeling.…”
Section: MC Involvement In Wound Healingmentioning
confidence: 99%
“…As mentioned above, MCs could activate synovial fibroblasts but also induce MMPs release by chondrocyte. Moreover, tryptase is recognized as a potent activator of MMPs [36].…”
Section: Mast Cells and Rheumatoid Arthritismentioning
confidence: 99%